Pengaruh Pertumbuhan Perusahaan, Profitabilitas Dan Ukuran Perusahaan Terhadap Nilai Perusahaan Pada Perusahaan Manufaktur Sub Sektor Barang Konsumsi Yang Terdaftar Di Bursa Efek Indonesia - Yulia Laila Faizra; Puteri Anggi Lubis; Laily - Ifazah; Muthmainnah - - (Jurnal Riset AKuntansi dan Bisnis, 2022)
This study aims to increase the influence of the company, profitability and company size on the consumer goods sub-sector manufacturing companies listed on the Indonesia Stock Exchange from 2014 to 2019. Several previous studies regarding the firm value of different results. Therefore, other research needs to be conducted to retest the theory of value.The results of this study partially indicate that company growth and profitability have a positive and significant effect on firm value. Meanwhile, company size has no effect on firm value. The results of the study simultaneously, profitability and firm size have a significant effect on firm value.